Pemahaman Peserta Didik Terhadap Permainan Monopoli Sebagai Media Pembelajaran Kelas Tinggi Di UPTD SDN 3 Karangtumaritis - Rafi Sulthan; , Luthfia Nur Afifah; Dea Nur Fatimah; Dewi Nopasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Elementary school education is a fundamental stage in the formation of character, mindset, and basic skills of students. In this phase, children are in the golden age of cognitive, affective, and psychomotor development, so creative and innovative learning strategies are needed. One approach widely recommended by educational experts is the use of game media to create a fun learning atmosphere, support students' learning process, and deepen their understanding of the material. Game media is also considered appropriate for the characteristics of elementary school children. Game media such as Monopoly, this learning media creates a fun and interesting atmosphere, thereby helping students improve memory, courage in expressing opinions, understanding the material, developing knowledge, and sensitivity to issues in the surrounding environment. Keywords: game media, elementary school learning, educational monopoly